An Effective Method for Generating Isolated Attosecond Pulses from a Solid Crystal Film - Wenwen Lv; Feng Wang; Congzhang Gao (Photonics)
Solids subjected to strong-field laser excitation can produce high harmonics, making high-order harmonic generation (HHG) one of the most effective methods for creating ultrafast coherent light sources, such as isolated attosecond pulses (IAPs). While extensive research has been conducted on generating IAPs through HHG in gaseous media, studies focusing on solid media are relatively limited. In crystals, the presence of numerous ionization and recombination sites, combined with high density and periodic structure, results in more complex interference dynamics. This complexity paves the way for unique applications in generating IAPs. Using an argon (Ar) crystal as a specific example, we have proposed and theoretically demonstrated an innovative approach for generating IAPs from a solid crystal film using a multi-cycle conventional driving laser pulse.